2023
DOI: 10.1021/acsmaterialslett.3c00085
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Nanoplates of Atomically Precise Co6S8 Cluster for Practical Arsenic Sensing

Abstract: Two-dimensional nanostructures with atomically precise building blocks have potential applications in catalysis and sensing. However, structural instability and surface reactivity limit their practical use. In this work, we demonstrate the formation of vertically aligned nanoplates of the [Co6S8DPPE6Cl6] cluster (Co6 in short), protected by 1,2-bis­(diphenylphosphino)­ethane, using ambient electrospray deposition (ESD). Charged microdroplets of Co6 formed by ESD on a water surface created such nanostructures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[2][3][4][5] Additionally, metal NCs exhibiting discrete energy levels present electronic transitions that resemble those in molecules inside the conduction band, express distinctive physical and chemical characteristics, and have significant uses in various fields, including ion sensors, cell labelling, and catalysis. [6][7][8][9][10][11] In the biological field, metal NCs have gained considerable attention owing to the fact that they possess outstanding features, including low toxicity, strong biocompatibility, and multifunctional surface chemistry. [12][13][14] Nowadays, wide varieties of metal NCs (Co, Ni, Cu, Ag, and Au) have been discovered that demonstrate superior catalytic functioning in hydrogenation, oxidation, CÀ N, and CÀ C coupling approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Additionally, metal NCs exhibiting discrete energy levels present electronic transitions that resemble those in molecules inside the conduction band, express distinctive physical and chemical characteristics, and have significant uses in various fields, including ion sensors, cell labelling, and catalysis. [6][7][8][9][10][11] In the biological field, metal NCs have gained considerable attention owing to the fact that they possess outstanding features, including low toxicity, strong biocompatibility, and multifunctional surface chemistry. [12][13][14] Nowadays, wide varieties of metal NCs (Co, Ni, Cu, Ag, and Au) have been discovered that demonstrate superior catalytic functioning in hydrogenation, oxidation, CÀ N, and CÀ C coupling approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Metal NCs, composed of particles ranging from one to a hundred atoms, are an emerging class of useful nanomaterials that address the void among more familiar organometallic substances and crystalline metal nanoparticles (Figure 1). [2–5] Additionally, metal NCs exhibiting discrete energy levels present electronic transitions that resemble those in molecules inside the conduction band, express distinctive physical and chemical characteristics, and have significant uses in various fields, including ion sensors, cell labelling, and catalysis [6–11] . In the biological field, metal NCs have gained considerable attention owing to the fact that they possess outstanding features, including low toxicity, strong biocompatibility, and multifunctional surface chemistry [12–14] …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal-ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, [22][23][24][25][26][27][28] an M 6 octahedron, [29][30][31][32][33][34][35] an M 13 cuboctahedron 36 and an M 7 decahedron, [37][38][39][40][41][42] among others, where 'M' represents Au, Ag, Cu, or other metal atoms or their mixtures. These fundamental polyhedral units can also be assembled through the sharing of vertices, edges, or faces, expanding the range of structural types for clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically precise metal clusters are a class of molecules that are well-known for their diverse properties. Their structural integrity, composition, and electronic confinement make them promising candidates for various applications. Over the past decade, exploring the reactions between atomically precise metal clusters has evolved as a new research area of interest. These reactions in the solution phase and in the gas phase have been probed using mass spectrometry. In such reactions, the exchange of metal atoms and ligands occurs, while maintaining the nuclearity of individual clusters. Neumaier et al have reported the kinetics of the reaction between the clusters [Au 25 (PET) 18 ] − and [Ag 25 (DMBT) 18 ] − in the solution .…”
Section: Introductionmentioning
confidence: 99%